Pengaruh Green Banking, Transformasi Digital, Kualitas Aset dan Efisiensi Operasional terhadap Kinerja Keuangan - Marshanda Cahyani Zahra; Virna Sulfitri (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2026)
This research aims to examine the impact of green banking, digital transformation, asset quality, and operational efficiency on the financial performance of banks in Indonesia from 2021 to 2024. Using a quantitative approach, the study employs panel data regression with the Random Effects Model (REM) through EViews software. The sample consists of 30 banks listed on the Indonesia Stock Exchange, with secondary data from annual reports, financial statements, and sustainability reports. Green banking is measured through a disclosure index, while digital transformation is represented by the ratio of digital intangible assets to total intangible assets. Asset quality is assessed using the non-performing loan (NPL) ratio, and operational efficiency is evaluated by the BOPO ratio. Financial performance is represented by net income, with Return on Assets (ROA) as a control variable. The findings indicate that green banking has a positive impact on financial performance, while digital transformation has a negative effect. Asset quality and operational efficiency, although important, do not significantly influence financial performance. ROA as a control variable shows a positive and significant impact. These results emphasize the need for strengthening green banking practices to promote sustainable financial performance in the banking sector.